The Manipulationist Threat to moral responsibility. - Moody, Kristoffer (Synthese, 2024)
Standard compatibilist accounts adjudicating when individuals are morally responsible for their actions are predicated on the assumption that individuals will have responsibility for the valuational structure undergirding their actions. However, I will claim that evidence from psychology and social psychology seems to show that manipulation of our valuational structure, far from being esoteric, is more common than we might pre-theoretically think. I call this evidence of manipulation the Manipulationist Threat. Given the Manipulationist Threat, I will argue that the strategies employed by reasons-responsiveness and Deep Self accounts for responding to manipulation are inadequate; they fail at either giving appropriate excusing conditions, or explaining why individuals subject to manipulation maintain responsibility.